Control of scabies, skin sores and haematuria in children in the Solomon Islands: another role for ivermectin - Lawrence Gregor; Leafasia Judson; Sheridan John; Hills Susan; Wate Janet; Wate Christine; Montgomery Janet; Pandeya Nirmala; Purdie David (Bulletin of the World Health Organization, 2005)
OBJECTIVE: To assess the effects of a 3-year programme aimed at controlling scabies on five small lagoon islands in the Solomon Islands by monitoring scabies, skin sores, streptococcal skin contamination, serology and haematuria in the island children. METHODS: Control was achieved by treating almost all residents of each island once or twice within 2 weeks with ivermectin (160-250 mg/kg), except for children who weighed less than 15 kg and pregnant women, for whom 5% permethrin cream was used. Reintroduction of scabies was controlled by treating returning residents and visitors, whether or not they had evident scabies. FINDINGS: Prevalence of scabies dropped from 25% to less than 1% (P < 0.001); prevalence of sores from 40% to 21% (P < 0.001); streptococcal contamination of the fingers in those with and without sores decreased significantly (P = 0.02 and 0.047, respectively) and anti-DNase B levels decreased (P = 0.002). Both the proportion of children with haematuria and its mean level fell (P = 0.002 and P < 0.001, respectively). No adverse effects of the treatments were seen. CONCLUSION: The results show that ivermectin is an effective and practical agent in the control of scabies and that control reduces the occurrence of streptococcal skin disease and possible signs of renal damage in children. Integrating community-based control of scabies and streptococcal skin disease with planned programmes for controlling filariasis and intestinal nematodes could be both practical and produce great health benefits.